2021
DOI: 10.4236/ojpm.2021.111004
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practices towards Hepatitis B Infection and Vaccination among Public Health Students in Ghana

Abstract: Background: Hepatitis-B (Hep-B) infection is a global public health problem of great concern which affects more than 5% of the local population in Sub-Saharan Africa. This study assessed students' knowledge, attitude and practices towards Hepatitis B infection and vaccination at the University of Health and Allied Sciences, Ghana. Methods: A cross-sectional quantitative descriptive survey was conducted among 262 Public Health students of the University of Health and Allied Science of the Volta region of Ghana,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…In addition, predictors associated with a high level of KAP were noticed. The results of this study showed a high level of knowledge of hepatitis B infection among MSs (54.5%), which is consistent with the results reported among MSs in studies in Ethiopia, Ghana, Senegal, Saudi Arabia, and Nepal [19][20][21]28], and these findings demonstrate the MS's solid foundation in HBV-related knowledge, which is critical for future healthcare professionals who will be at the forefront of patient treatment. However, the result was inconsistent with studies done in Syria and Ethiopia [11,18].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, predictors associated with a high level of KAP were noticed. The results of this study showed a high level of knowledge of hepatitis B infection among MSs (54.5%), which is consistent with the results reported among MSs in studies in Ethiopia, Ghana, Senegal, Saudi Arabia, and Nepal [19][20][21]28], and these findings demonstrate the MS's solid foundation in HBV-related knowledge, which is critical for future healthcare professionals who will be at the forefront of patient treatment. However, the result was inconsistent with studies done in Syria and Ethiopia [11,18].…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, MSs are potential future physicians and leaders, and these students need to understand the epidemiology, determinants, screening, and management of HBV to promote effective prevention, early diagnosis, and successful treatment [11]. However, the level of awareness toward HBV infection among undergraduate MSs varies globally [18][19][20][21]. Consequently, it is important for the medical colleges to identify areas of weakness in MSs and actively contribute to the training and development of the future generations of medical practitioners.…”
Section: Introductionmentioning
confidence: 99%
“…The high pro-vaccine perception rate could be attributed to the fact that the majority of the respondents have also reported a good knowledge level of HBV infection. Furthermore, most of the respondents (76.9%) believe that they are in danger of acquiring HBV infection because of the nature of their work, this result is higher than that reported in Ghana (54.6%) (31). Overall, the good level of knowledge of HBV infection (Table 2), positive perception towards Hep B vaccination, and the good risk perception rate reported in this study could partially re ect the awareness level of the respondents as clinical-level medical students.…”
Section: Discussionmentioning
confidence: 65%